Evaluation of inoculation methods for screening pearl millet against smut disease - and D.P. THAKUR, M.S. YADAV, J.C. DUHAN (Indian Phytopathology, 2002)
Smut caused by Tolyposporium penicillariae Bref. is the most common and widespread disease of pearl millet in India. Evaluation of genetical materials against the disease under severe epiphytotic conditions is essential. Creation of severe and effective infection conditions through artificial inoculation procedure is, thus, the key to success for the effective screening procedure. Previously, screening was done by using syringe inoculation method during boot stage with sporidial suspension (1 x 10~6sporidia/ml) or by spraying at early stigma to full stigma emergence stage with the same sporidial suspension concentration. Perusal of literatures show that dip inoculation method was not tested by research workers for screening purpose against this disease. Therefore, present studies were conducted to evaluate the efficacy of this method along with two other methods for screening pearl millet against smut infection, under artificial epiphytotic conditions.